Capsaicin: preclinical and clinical studies - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
Drugs obtained from plant sources occupy important position in different pharmacopoeias. Many of the life saving drugs in the present day allopathic system are obtained from plant origin only. Extensive scientific research on capsaicin, a natural compound, pungent principle, present in the fruits of plant Capsicum anum, has been performed. In preclinical studies capsaicin shows lipid lowering by stimulating its metabolism, gastroprotection against aspirin and ethanol induced ulcers. Capsaicin in rodents shows anticancer activity against NKK induced lung and liver cancer. It also exhibits antidiabetic, antimicrobial, anti-inflammatory and antioxidant properties in rodents. In clinical studies Capsaicin shows gastroprotection in healthy volunteers. In double blind studies capsaicin proved to be useful in skin disorders against prutitic psoriasis and prurigo nodularis with randomized double blind studies. It also exhibits good analgesic activity against post-therapeutic neuralgia, osteo-arthritis, rheumatoid arthritis and diabetic neuropathy. Capsaicin is fairly safe with oral dose 0.5-1.0 mg/kg.
Keywords: capsaicin; Capsicum anum; clinical studies; preclinical